Von der Umwelt zur Welt: Der Weltbegriff in der Umweltsoziologie - Block, Katharina (transcript, 2016)
»Environment« has become an overused buzzword that also is at the forefront of the academic debate, since it promises enlightenment and resolution. An interrogation of environmental sociology informed by the theory of science, which is fundamentally present here, seems to be offered. Katharina Block places the focus on the question of anthropological abbreviations which are systematically associated with the concept of the environment, and in a countermotion, employs the concept of the world to create the possibility of casting off these anthropologisms which have been exposed, and of seeking out new socio-theoretical connections. As such, this study is of interest for all disciplines that deal with the highly contemporary topic of human-environmental relations.